Effectiveness of Classical Guidance Utilizing Applications Kahoot In Forming Student Character Through Improving Student Interpersonal Communication - Nur Afifah Nabila Saragih; Firman Firman; Mohd. Suhadi Bin Mohamed Sidik (Jurnal Counseling Care, 2024)
Good interpersonal communication is a reflection of an individual's character. This character is formed from character education. Therefore, it is necessary to improve interpersonal communication among individuals. The aim of this research is to determine the effectiveness of classical guidance services using the Kahoot application in forming student character through improving interpersonal communication. This research is quantitative research with a positivistic paradigm. This research uses an experimental method, the experimental method used is a Quasi Experiment with a One-Group Pretest-Posttest research design Design by providing pre-test and post-test . The population in the study were students of Padang Public High School 1. The sample for this research was class XI F12 students with a total of 33 people. The research sample was selected using purposive sampling technique. The instrument used in this research was a questionnaire with a student interpersonal communication scale. Analysis of this research data used the Wilcoxon test . The results of the research revealed that when carrying out the pre-test, 20 students had poor interpersonal communication and after being given the post-test, 33 students had good interpersonal communication. From the results of the Wilcoxon test, the results obtained were J ℎ ?????<J?????, namely 3.4<170, meaning that the hypothesis is accepted, namely that there are differences in interpersonal communication before and after being given classical guidance services using the Kahoot application. It can be concluded that classical guidance services using the Kahoot application are effective in improving students' interpersonal communication as a form of character education for students.